A South Indian Digest of Commentaries on the Nyāyasūtra : Gambhīravaṃśaja’s Nyāyasūtravivaraṇa—First Adhyāya - Oliver Philipp Frey (Brill, 2023)
The Nyāyasūtravivaraṇa, written in the first centuries of the 2nd millennium CE, provides the most accessible introduction to the core teachings of old Nyāya. Excerpting from the two earliest and most important treatises of this tradition—the Nyāyabhāṣya and Nyāyavārttika—Gambhīravaṃśaja created a comprehensive yet concise digest. The present work contains not only a critical edition of the first chapter based on all known textual sources but also a complete documentation of the variants, a comprehensive study of the parallel passages, a detailed discussion of the preparation and processing of the text-critical data, and a detailed documentation of the Grantha Tamil, Telugu and Kannada scripts.